Lessons to be learnt in managing the breech presentation at term: An 11‐year single‐centre retrospective study. (17th April 2014) - Borbolla Foster, Ailsa; Bagust, Annalise; Bisits, Andrew; Holland, Matthew; Welsh, Alec
<x xml:space="preserve">Abstract</x> Background The 2000 publication of the Term Breech Trial significantly impacted obstetric practice in Australia with a rapid increase in delivery of term breech singletons by caesarean section. More reassuring data from European centres who continued to offer vaginal breech deliveries to carefully selected women have led to a softening of international guidelines which now support an individualised approach to management. The application of this principle to an Australian population, particularly in the wake of such a major change in obstetric practice, has not previously been demonstrated. Aim To compare short‐term neonatal and maternal morbidity for infants with a singleton breech presentation born after 37 weeks, according to planned mode of delivery. Materials and Methods Eleven‐year single‐centre retrospective study with intention‐to‐treat analysis based on intended mode of delivery. Results Two hundred and forty‐three of 766 (31.7%) eligible women elected for planned vaginal breech delivery. The overall success rate in this group was 58%. Morbidity rates were low and compare favourably with similar international studies. However, there was a nonsignificant trend towards higher rates of short‐term serious neonatal and maternal morbidity in the planned vaginal delivery group (1.6 vs 0.4%, P = 0.08 and 8.2 vs 4.8%, P = 0.06, respectively). Conclusions Attempted vaginal delivery for breech presentation remains an option in carefully selected women under strict obstetric protocols.